THE EFFECT OF SOME ATTRACTIVE MEDIA ON THE NUMBER OF MARRIAGE PARTNERS, EGGS WEIGHT AND LIFETIME OF BLACK SOLDIER FLY (Hermetia illucens L.) - Syafrina Lamin; Arfan Abrar; Arwinsyah Arwinsyah; Mustafa Kamal; Agnes Novita Sipahutar (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
The black soldier fly (BSF) Hermetia illucens L.(Diptera:Stratiomyidae) is widely used in biorecycling organic waste has gained huge populatarity in different industrial. And commercial sector becouse of its excellent potential to treat organic waste and high biomass production. The obstacle experienced during the rearing process was that a small number of eggs were obtained, therefore efforts were made to increase the black soldier fly population by providing bait in the form of attractants. Media bait technique in the form of several media with a specific and pungent aroma, so that it will lure BSF females to mate, lay eggs, extend life time. The present study deal to investigation of different number of mating pairs, eggs weight dan lifetime as function respon of different lure media.This study used a completely randomized design (CRD) with (1) cassava tape, (2) Fermented bran (3) rotten pineapple (4) rotten banana media with each treatment repeated 6 times with the variables observed were the number of mating pairs of fly (per day), egg weight, and life span of imago. each attractant medium had an effect on the number of mating females, the weight of the eggs laid and the length of life of BSF. The best medium was rotten pineapple media (number of mating pairs 55 pairs of BSF, and egg weight laid 0.007 per day) while the worst medium was fermented bran media with a long life (10.9 days)